PRE-STROKE PHYSICAL ACTIVITY IN RELATION TO POST-STROKE OUTCOMES: A SYSTEMATIC REVIEW - Prasetyo, Rosyid; Nuswantoro, Yoga Nuswantoro; Anggraini, Efa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Stroke has a direct impact on overall health. The interval between the onset of symptoms and arrival at the hospital can greatly influence the effectiveness of treatment and patient prognosis. Stroke survivors are additionally affected by long-term physical and psychosocial well-being. The aim: This study aims to show pre-stroke physical activity in relation to post-stroke outcomes. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 74 articles, whereas the results of our search on SagePub brought up 77 articles. The results of the search conducted for the last year of 2013 yielded a total 7 articles for PubMed and 54 articles for SagePub. The result from title screening, a total 5 articles for PubMed and 31 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: People who were physically active before the stroke tended to be more independent in physical functioning after the stroke. Regardless of physical activity before stroke, all patients demonstrated improvements in mobility, walking ability, and upper extremity self-perception during functional treatment.